Clinical researchChanges in attainment of lipid goals by general practitioners and specialists in patients at high cardiovascular risk in Hungary during 2004-2008 - Mark, Laszlo; Paragh, György; Karadi, Istvan; Reiber, Istvan; Pados, Gyula (Archives of Medical Science, 2010)
Introduction : Lipid-lowering therapy should achieve target levels. We assessed the change of the achievement of targets and the mean low-density lipoprotein cholesterol (LDL-C) levels in high-risk Hungarian patients. Material and methods : Six studies performed with patients of general practitioners (GPs) and specialists between 2004 and 2008 were evaluated: 9,508 patients from GPs and 2809 from specialist practices (total 12,317). Results : During this 4-year period the LDL-C level decreased by 0.73 mmol/l and the LDL-C goal achievement rate increased from 14 to 32% in patients treated by GPs. LDL-C showed a decrease of 0.48 mmol/l and the goal achievement rate changed from 20 to 43% in patients treated by specialists. In the majority of the patients not achieving the LDL-C goal (57% for specialists and 89% for GPs) there was no modification in the current therapy. In addition to emphasizing the priority of LDL-C lowering, we should also strive for residual risk reduction, which means raising high-density lipoprotein cholesterol (HDL-C) and lowering triglyceride levels. There was no significant improvement in HDL-C or triglyceride levels during the examined period. Conclusion : More attention needs to be paid to changing treatment of patients to achieve target levels.